Investigation into an automated container yard - Pang, Andrew Li Jian (2009)
Globalization has drastically increased the amount of trade between different nations and this has lead to an exponential growth in shipping activities around the world. As a result, many container terminals are struggling to cope with this new surge of containers moving through their yards. Hence numerous container terminals are looking into varies ways to handling this new high volume of container traffic given a limited land area available to them. One such way which many are looking at currently is the possibility of automating their container terminal so as to dramatically provide their operational efficiency and hence be able to handle higher container traffic at their terminals. There are currently a few automated container terminal designs which have been proposed and implemented in the industry. However, many container terminals are unwilling to adopt these current concepts due to the uncertainty of actual operational performance of these concepts and the high setup cost involved in adopting these concepts. In this project, a study was conducted into the conceptualization of a new automated container terminal. During the initial phase of the project, a detailed literature review was conducted on current automated container terminals to understand the limitations of current automated container terminal concepts and to better capture the needs and requirements of container terminals around the world. Based on the information gathered as well as from the analysis of each automated container terminal concept, a new automated container terminal termed the Linear Motor Automated Storage and Retrieval System (LM-AS/RS-ACT) was conceptualized. A simulation was performed on the new conceptual model using Arena simulation software and the results of the simulation proved that the LM-AS/RS ACT was able to achieve a ship turnaround time of 16 hours while utilizing significantly less land area as compared to other ACT concepts. However, the LM-AS/RS-ACT has a significantly high start up cost which is currently a major drawback. Hence, future development is proposed at the end of the report on possible ways to reduce the start-up cost and make the LM-AS/RS-ACT a promising future automated container terminal design.